2009
DOI: 10.1097/iae.0b013e31818a1fd3
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up of Combined Customized Therapy. Photodynamic Therapy and Bevacizumab for Exudative Age-Related Macular Degeneration

Abstract: Combined, customized PDT + Bevacizumab therapy makes it possible to obtain visual results similar to those obtained in monotherapy, but with fewer intravitreal injections. It appears to be an interesting option for this type of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In a previous series of our study, comprising 63 cases with a 12-month follow-up, 18 we obtained a gain of 5.7 letters with a mean of 1.4 PDTs and 2 bevacizumab doses per patient compared with the 7.2 letters with 1.2 PDT and 2.3 ranibizumab intravitreal injections in this series. The loss and gain rates of vision are practically the same except for the group of patients with visual gains of .15 letters, which is better with PDT + ranibizumab (19% as opposed to 32.7%).…”
Section: Discussionmentioning
confidence: 81%
“…In a previous series of our study, comprising 63 cases with a 12-month follow-up, 18 we obtained a gain of 5.7 letters with a mean of 1.4 PDTs and 2 bevacizumab doses per patient compared with the 7.2 letters with 1.2 PDT and 2.3 ranibizumab intravitreal injections in this series. The loss and gain rates of vision are practically the same except for the group of patients with visual gains of .15 letters, which is better with PDT + ranibizumab (19% as opposed to 32.7%).…”
Section: Discussionmentioning
confidence: 81%
“…Mean numbers of retreatment per eye were 0.57 during the 12 month follow up. Navea et al treated 63 patients using bevacizumab intravitreal injection followed by PDT for 12 months [16]. The mean numbers for additional PDT and additive bevacizumab injections per patient were 0.46 and 1.0, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several uncontrolled studies and case series have shown anatomical improvement and moderate vision gain when bevacizumab was used as a monotherapy [8-12]. However, repeated intravitreal injections are subject to the risk of complications, discomfort for the patient, and increased health care expense [13-16]. …”
mentioning
confidence: 99%
“…In particular, over the last few years, the anti-CNV therapies evolved from protocols aimed at stabilizing a patient’s vision ( i.e ., quarterly execution of PDT-V procedure) [ 11 , 14 , 15 , 16 , 17 ], to treatments capable of improving visual acuity ( i.e ., monthly or as-needed intravitreal administration of anti-VEGF drugs) [ 12 , 13 , 18 , 19 , 20 , 21 , 22 ]. After all, considering not only the visual benefit and its maintenance but also a lower re-treatment frequency and optimization of health resource employment, positive outcomes are observed when PDT-V is combined with anti-VEGF regimens [ 6 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%